2020
DOI: 10.1126/sciadv.abb0295
|View full text |Cite
|
Sign up to set email alerts
|

In search of opportunity and community: Internal migration of refugees in the United States

Abstract: At a time of heightened anxiety surrounding immigration, state governments have increasingly sought to manage immigrant and refugee flows. Yet the factors that influence where immigrants choose to settle after arrival remain unclear. We bring evidence to this question by analyzing population-level data for refugees resettled within the United States. Unlike other immigrants, refugees are assigned to initial locations across the country but are free to relocate and select another residence after arrival. Drawin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
(24 reference statements)
2
14
0
Order By: Relevance
“…The majority of studies have found that immigrants tend to concentrate in specific countries (De Giorgi and Pellizzari, 2009;Razin and Wahba, 2015;Agersnap et al, 2020) and regions (Borjas, 1999;Dodson, 2001;Åslund, 2005;Fiva, 2009;Dellinger and Huber, 2021) with generous welfare benefits, consistent with the welfare magnet hypothesis. However, other work has found evidence that immigrants tend to prioritize employment or co-ethnic networks over welfare considerations when selecting residential locations within destination countries (Zavodny, 1999;Kaushal, 2005;Mossaad et al, 2020). This empirical ambiguity can be traced, in part, to issues of data availability and research design.…”
Section: Forthcoming American Journal Of Political Sciencementioning
confidence: 99%
“…The majority of studies have found that immigrants tend to concentrate in specific countries (De Giorgi and Pellizzari, 2009;Razin and Wahba, 2015;Agersnap et al, 2020) and regions (Borjas, 1999;Dodson, 2001;Åslund, 2005;Fiva, 2009;Dellinger and Huber, 2021) with generous welfare benefits, consistent with the welfare magnet hypothesis. However, other work has found evidence that immigrants tend to prioritize employment or co-ethnic networks over welfare considerations when selecting residential locations within destination countries (Zavodny, 1999;Kaushal, 2005;Mossaad et al, 2020). This empirical ambiguity can be traced, in part, to issues of data availability and research design.…”
Section: Forthcoming American Journal Of Political Sciencementioning
confidence: 99%
“…We have also benefited from seminar participants at the University of San Francisco, UC Davis Economics Alumni Conference, and the EARN Workshop for Integration hosted by the University of Copenhagen. 5 Using a longer time window and earlier study period, Mossaad et al (2020) estimate that from 2000-2014 17% of refugees moved between states within two years of their arrival. Not only is the time window wider but also interstate mobility has trended downward in the US since 2000 (Molloy, Smith, and Wozniak 2011).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We discuss our analysis of ORR data in the Appendix.5 Using a longer time window and earlier study period,Mossaad et al (2020) estimate that from 2000-2014 17% of refugees moved between states within two years of their arrival. Not only is the time window wider but also interstate mobility has trended downward in the US since 2000(Molloy, Smith, and Wozniak 2011).6 Based on tests shown in the Appendix, we find no evidence for the possibility that the Executive Order affected the migration choices of natives and other residents.…”
mentioning
confidence: 99%
“…Predominantly White neighborhoods may have more options in the face of natural hazards (Howell and Elliott 2019;Elliott 2015). Also, although people may move to a region with more employment opportunities, they may be specifically drawn to areas where job openings specific to their skills are abundant (Mossaad et al 2020). We thus include a share of manufacturing sector employees in a county using employment data by industry retrieved from NAICS.…”
Section: A Confounding Variablesmentioning
confidence: 99%